Antecedents of panic buying in supermarkets during the early phase of the Covid-19 pandemic: The direct effect of Perceived Scarcity, Emotions, and Social Media Information Overload - Aufa Shandra Tama; Syafrizal Syafrizal; Rahmat Eka Putra (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2022)
One of the main factors that cause panic buying is a crisis situation. The global Covid-19 outbreak has prompted consumers to panic buying. Especially experienced by consumers of retail stores in the city of Padang (West Sumatra-Indonesia). This phenomenon prompted researchers to examine the effect of perceptions of product scarcity, emotions, and social media consumption on panic buying in the city of Padang. Total of 125 samples were obtained through an online survey questionnaire. The data were analyzed using the Structural Equation Model with the SmartPLS statistical tool. The results of the study show that emotions and social media information have a positive and significant influence on panic buying. However, the perception of scarcity has no significant effect on panic buying. The results of the study are then discussed and have implications for the development of theory and practice.